1993
DOI: 10.1159/000261528
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Fluoride Release of Visible Light-Activated Composites in vitro: A Correlation with in situ Demineralisation Data

Abstract: Fluoridated composites are able to reduce or inhibit secondary caries around fillings. The aims of this study were firstly to investigate the amount of F released in vitro from composites with a F content between 0 and 26 vol% as a function of time over a 1-year period. A second aim was to correlate the in vitro data on F release with enamel demineralisation data in situ after a 1 -month period. The results show that all fluoridated composites release sizable amounts of F in solution, the total amounts of F re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0
3

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 11 publications
2
44
0
3
Order By: Relevance
“…Approximately 200-300 µg/cm 2 a month of fluoride ion are needed to prevent enamel demineralization 36) . In the present study, the accumulated amounts of fluoride during the first 14 days from the A100-and A100f-GICs were 161.1 and 218.3 µg/ cm 2 , respectively, whereas that of the control-GIC was 97.6 µg/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 200-300 µg/cm 2 a month of fluoride ion are needed to prevent enamel demineralization 36) . In the present study, the accumulated amounts of fluoride during the first 14 days from the A100-and A100f-GICs were 161.1 and 218.3 µg/ cm 2 , respectively, whereas that of the control-GIC was 97.6 µg/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, ytterbium fluoride is used in several products (i.e., Heliomolar RO, Helioprogress, and Tetric from Ivoclar), and substantial fluoride has been shown to be released from these materials for up to five years (Arends and Ruben, 1988). A recent study examining in situ demineralization and fluoride release from these composites demonstrated that enamel demineralization decreased as fluoride release increased (Dijkman et al, 1993). By extrapolation of the data, the authors predicted that a composite that released 200-300 |iig/cm 2 fluoride over a one-month period would completely inhibit secondary caries under plaque conditions.…”
Section: (B) Recent Areas Of Studymentioning
confidence: 99%
“…Therefore, despite the fact that these fluoridated composites release significant amounts of fluoride, their present ability to prevent secondary caries is questionable, and improvements in technology will be required to increase the level of fluoride release. Dijkman et al (1993) showed that a composite with a fluoro-aluminum silicate filler released an order of magnitude more fluoride than Heliomolar, and that the fluoride release rate increased in a linear manner with time. This was hypothesized to be due to the greater water solubility of the silicate filler in comparison with ytterbium fluoride.…”
Section: (B) Recent Areas Of Studymentioning
confidence: 99%
“…OGLC also had a better behavior compared to MCB and FOLC. Although FOLC had significantly lower fluoride release than the other three RRGICs, this process was detectable and superior to that of TXT during the whole experiment, which is crucial in the orthodontic treatment (17).…”
Section: Discussionmentioning
confidence: 78%